Effects of cooking methods of Thai Spice Sausage on chemical composition and sensory evaluation - Pripwai N. (2014)
Thai Spice Sausage is fresh sausage and originates from the northern of Thailand. The preparation is: minced pork consisting of trimmed-pork: fat (1:1 w/w) is mixed thoroughly with chili paste which consists of dry chili, lemon grass, shallot, garlic, curcumin, salty shrimp-like paste, coriander root, lime-like leaf and galanga. The ratio of minced pork and chili paste was 1:0.25 w/w and cased in the rehydrated natural casing by hand. The raw Thai Spice Sausage was stored at 4°C for 24 hours before cooking. The raw Thai Spice Sausage was further processed with three different cooking methods, namely; roasting, frying and grilling. It was found that dry matter of 3 cooking methods were 42.28%, 44.29% and 47.76%, respectively (p<0.05). Crude protein of frying method was significantly higher than roasting and grilling method (22.20% and 20.88%), respectively. Cooking loss of frying method was lower than roasting and grilling method (37.82% and 24.84%; p<0.05); respectively. Water activity of frying method had no difference from roasting method but was significantly lower 3.45% than grilling method. There were no significant differences in ether extract and shear value. According to the sensory evaluation of Thai Spice Sausage for ideal ratio score in terms of diameter and tenderness, overall acceptance of frying method was significantly higher than the other two cooking methods. It was concluded that frying method of Thai Spice Sausage could prolong shelf life and yield more benefit.